1998
DOI: 10.1161/01.cir.97.12.1144
|View full text |Cite
|
Sign up to set email alerts
|

Regional Myocardial Blood Flow Redistribution as a Cause of Postprandial Angina Pectoris

Abstract: Background-Postprandial angina pectoris has been recognized for more than two centuries and can be identified in up to 10% of patients with chronic ischemic heart disease. Redistribution of myocardial blood flow, from a region supplied by a severely stenotic coronary artery to those supplied by less diseased or normal vessels, is a potential mechanism of postprandial angina. Methods and Results-To test this hypothesis, we have determined the effects of a standard liquid meal on whole heart and regional myocard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…Kearney et al [7] suggested that increased ischemia magnitude in patients with coronary disease during exercise after a carbohydrate but not a high fat meal (HFM) could be explained by paradoxical coronary constriction in response to an insulin mediated increase in coronary flow. This conclusion is supported by Baliga et al [21], who studied myocardial blood flow with positron emission tomography before and after a liquid meal. Whole heart blood flow increased after the meal, but there was redistribution of flow away from territories supplied by severely narrowed arteries, consistent with constriction in flow-limiting segments of the coronary artery diameter after food intake.…”
Section: Mechanisms Of Reduced Ischemic Threshold After Hcmsupporting
confidence: 52%
“…Kearney et al [7] suggested that increased ischemia magnitude in patients with coronary disease during exercise after a carbohydrate but not a high fat meal (HFM) could be explained by paradoxical coronary constriction in response to an insulin mediated increase in coronary flow. This conclusion is supported by Baliga et al [21], who studied myocardial blood flow with positron emission tomography before and after a liquid meal. Whole heart blood flow increased after the meal, but there was redistribution of flow away from territories supplied by severely narrowed arteries, consistent with constriction in flow-limiting segments of the coronary artery diameter after food intake.…”
Section: Mechanisms Of Reduced Ischemic Threshold After Hcmsupporting
confidence: 52%
“…14,15 Digestion in mammals does not increase the metabolic rate for as long or proportionally as much as it does in reptiles, and it takes weeks rather than days of sustained hemodynamic overload to develop a full, stable cardiac hypertrophic response in mammals. However, there is an analogous condition in humans in which a prolonged but reversible increase in cardiac workload produces reversible cardiac hypertrophy: pregnancy.…”
Section: Fuzzy-o-logical Hypertrophy?mentioning
confidence: 99%
“…This could contribute to a "horizontal" steal of blood from lasered to nonlasered regions as previously reported in patients with coronary heart disease. 29,30 Moreover, experimental evidence of a reduction in flow distribution to the endocardium during exercise in a denervated area of the LV subtended by a stenotic artery 31 also needs to be considered. These mechanisms could be responsible for the worsening of the wall motion score index during dobutamine infusion after TMLR described by Frazier and coworkers.…”
Section: Ii-136 Circulation November 9 1999mentioning
confidence: 99%